The moderating role of stakeholder management and societal characteristics in the relationship between corporate environmental and financial performance. (15th July 2018) - Dal Maso, Lorenzo; Mazzi, Francesco; Soscia, Manuel; Terzani, Simone
Abstract: This study contributes to the debate about the moderating factors that affect the relationship between environmental and financial performance. Combining stakeholder theory, stakeholder salience, and legitimacy theory, and based on a large international sample, we demonstrate that stakeholder prioritization and engagement jointly positively moderate the relationship between environmental and financial performance. However, this moderating effect is only found when both formal and informal societal characteristics are strong and support the business environment surrounding the firm and its stakeholders. Contributions and implications for managers and regulators are discussed. Highlights: We combine stakeholder theory, stakeholder salience, and legitimacy theory. We examine moderators of the environmental-financial performance relationship. Stakeholder prioritization/engagement positively moderate the CEP-CFP relationship. This result holds only when firms jointly implement prioritization and engagement. Strong formal-informal institutions are essential for enabling the moderating effect.